2007
DOI: 10.1016/j.rmed.2006.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The impact of long-term conventional treatment for overlap syndrome (obstructive sleep apnea and chronic obstructive pulmonary disease) on concurrent erectile dysfunction

Abstract: Conventional treatment for OSA and COPD, has a positive effect on concurrent ED on the minority of patients. This effect is possibly due to the improvement of respiration during sleep with CPAP and of oxygenation with bronchodilators continuously. Of the improved men, one third was not satisfied with the impact of this treatment modality on their EF. It is likely that specific for ED treatment is needed in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
7
0
4
Order By: Relevance
“…1). De este modo, encontramos diferencias significativas (p = 0,023) entre pacientes con disfunció n leve (41 [21] apneas-hipopneas/hora) y grave (63 [18] apneas-hipopneas/ hora).…”
Section: Resultsunclassified
See 3 more Smart Citations
“…1). De este modo, encontramos diferencias significativas (p = 0,023) entre pacientes con disfunció n leve (41 [21] apneas-hipopneas/hora) y grave (63 [18] apneas-hipopneas/ hora).…”
Section: Resultsunclassified
“…The prevalence of ED was 69%. We found significant differences in AHI between patients with mild and severe ED (41 [21] vs 63 [18], P = .023). ED was associated with hypertension (odds ratio [OR] = 3.56 [1.64-7.72]), hypercholesterolemia (OR = 7.19 [2.39-21.68]), diabetes mellitus type 2 (OR = 3.07 [1.02-9.48]) and ischemic heart disease (OR = 1.51…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…20 Although further study should be conducted to investigate the relationship between NO and OSAS, the impairment of the vasoprotective function of NO as a result of respiratory disturbances during nighttime sleep may explain the association between OSAS and ED. 21 Testosterone has been proposed as another linking factor between ED and hypoxia, though it is controversial. Kö hler et al 22 reported that androgen deficiency was quite common in men with ED.…”
Section: Erectile Dysfunction In Osas H-w Shin Et Almentioning
confidence: 99%